The Role of Pirls Research in the Formation of Library Culture in Students - Rabbonayeva Dildora Tolipovna (Researchparks Publishing, 2021)
The article discusses the approach to the issue of reading in our society and the role of PIRLS research in shaping the culture of reading in primary school students